Preliminary design and analysis of masonry infilled R/C frame based on storey drift limitations subjected to lateral loads - Hashmi, Arshad K. (Journal of Structural Engineering, 2024)
Multistorey building design is a complex and iterative processes. Recent codal requirements have made it more difficult and intricate. Serviceability criterion for lateral deflection (drift) is one of such requirements which play a vital role in the iterative design process. A preliminary design with satisfied storey drift limitations reduces the number of iterations in the multistory building design processes and provides a tentative member dimensions for designer to start with. The present study deals with enhancement of one such preliminary design procedure and development of its computer program. The enhanced preliminary design is for lateral loads (i.e. wind and seismic) which satisfies the storey drift limitation specified by the code of practice. The present paper incorporates the preliminary design for masonry infilled soft ground storey R/C frame (a seismically vulnerable and common structure) as well based on codal provision. The other objective of the study is to demonstrate the performance of the preliminary design under lateral load. The present study applies virtual work theory for the preliminary design procedure of R/C frame members where as it employs pushover analysis and nonlinear dynamic time history analysis for conforming the performance of the preliminary design.